Elucidating the role of hyaluronic acid in the structure and morphology of calcium oxalate crystals - POLAT, SEVGİ (ELSEVIER, 2021)
Recent surge in reports describing new additives that inhibiting the growth and nucleation of calcium oxalate (CaOx), the most common component of renal calculi or kidney stones, have rekindled interest in CaOx crystallization. In this in vitro study, the effect of hyaluronic acid (HA), a protein commonly found in urine, on the morphology and phase of the CaOx crystals is investigated. CaOx crystals were crystallized at pH 5.8 and 37 degrees C with a [Ca2+]:[C2O42-] ratio of 20:1, which is close to physiological conditions, in aqueous solution and artificial urine media. The obtained crystals were characterized structurally, morphologically and in terms of their surface charge. The crystals precipitated in aqueous solution without the HA additive were pure phase calcium oxalate monohydrate (COM) crystals with typical hexagonal morphology. The addition of HA partially promotes the transformation of COM into calcium oxalate dihydrate (COD) in aqueous solution. However, the only solid phase to form in artificial urine media with and without HA was identified as COD with tetragonal bipyramidal morphology. The results of this investigation will contribute to the understanding of the role HA plays on the morphology, structure, and thermal characteristics of CaOx and ultimately facilitate the development of effective treatments for kidney stones. (C) 2021 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Calcium oxalate; Crystallization; Hyaluronic acid; Morphology; Kinetics; THERMAL-TREATMENT; ZINC IONS; GROWTH; CRYSTALLIZATION; MONOHYDRATE; SURFACE; NANOPARTICLES; WHEWELLITE; INHIBITION; WEDDELLITE